Supervised Deep Breathing Exercises Improve Functional Aerobic Capacity in Patients with Severe Spinal Deformity: Quality, Safety and Value (QSVI) - Zapata, Karina A.; Kayla M. Clem; Rupha H. Stevens; Charu Sharma; McIntosh, Amy L. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Background: Our institution has traditionally treated children with severe spine deformity using halo gravity traction (HGT) to improve curve magnitude and increase flexibility. Local Problem: Assessing the non-radiographic benefits of HGT such as pulmonary function, is difficult. Pulmonary function is commonly reflected by pulmonary function testing (PFT) which is dependent on MAXIMAL patient effort. Six-minute walk test (6MWT) reflects functional exercise capacity. Specific Aims: This quality initiative (QI) was performed to evaluate the addition of supervised deep breathing exercises (DBE) utilizing an incentive spirometer (IS) to supervised physical therapy exercise in patients with severe spinal deformity that require HGT. Methodology: A QI core team was established with the aim of improving the pulmonary function aspect of our HGT program. The team consisted of 1 orthopaedic surgeon, 1 quality improvement program manager, 2 physical therapists (PTs), and 1 respiratory therapist (RT). The QI core team met every 4 to 6 weeks to discuss patients and processes. Intervention: RTs supervised HGT patients performing DBE 4 times per day, and asked families to independently perform DBE 4 additional times per day. PTs performed the six-minute walk tests (6MWT). A pulse oximeter was used to monitor oxygen saturation levels. RTs performed the PFTs. The 6MWT and PFTs were performed prior to halo application, and every 2 weeks while in HGT treatment. Results: The intervention HGT patients who received supervised DBE (n=14) demonstrated significantly improved 6MWT scores from 1440±546 feet pre-halo to 1663±398 feet pre-surgery (p=0.02). A historic cohort of HGT patients who did not receive supervised DBE (n=10) demonstrated no significant changes in 6MWT scores at 1493±391 feet pre-halo and 1477±406 feet pre-surgery. Averaged forced vital capacity worsened 4±10% and average forced expire volume in one second worsened 1±8%. Conclusions: Children in HGT undergoing supervised DBE and physical therapy demonstrate improved functional aerobic capacity according to the 6MWT despite no improvement in pulmonary function tests.